Domination of phononic scattering in solid solutioning and interfaces of HfB2–ZrB2 – SiC -carbon nanotube based ultra high temperature composites. (September 2022) - Dubey, Shruti; S, Ariharan; Nisar, Ambreen; Saini, Sudha; Jana, Subhra S.; Wangaskar, Bhimashankar; Das, Amit; Khandekar, Sameer; Maiti, Tanmoy; Omar, Shobit; Balani, Kantesh
Abstract: HfB2 -ZrB2 based ultra-high temperature ceramics (UHTCs) are used as protective tiles for nose cones and leading edges of the hypersonic vehicles that face harsh service conditions of temperatures >2000 °C. The present work assesses the effect of SiC (20 vol.%) and carbon nanotubes (CNT, 6 vol.%) incorporation on isolating the phononic and electronic contribution to thermal conductivity of spark plasma sintered HfB2 -ZrB2 based UHTCs. Except HfB2 -SiC, all ZrB2 based UHTC composites elicited similar electrical conductivity (∼ 5.7 × 10 6 S/m), whereas a marginal increase of ∼9% in thermal conductivity was observed with CNT reinforcement in HfB2 -ZrB2 –SiC composites. With HfB2 /ZrB2 -SiC composites eliciting high thermal conductivity (120–150 Wm -1 K -1 ), the current work emphasizes the domination of phononic scattering (by ∼44%) due to solid solutioning in HfB2 -ZrB2 -based ceramics. Further, electronic thermal scattering events may only be marginal at interfaces of CNT and ZrB2, and limit thermal scattering in HfB2 /ZrB2 -SiC-CNT based UHTCs for hypersonic applications. Graphical abstract: Image, graphical abstract